The Theatre of Shelley - Mulhallen, Jacqueline (Open Book Publishers, 2010)
This is the first full-length study of Shelley's plays in performance. It offers a rich, meticulously researched history of Shelley's role as a playwright and dramatist and a reassessment of his "closet dramas" as performable pieces of theatre. With chapters on each of Shelley's dramatic works, the book provides a thorough discussion of the poet's stagecraft, and analyses performances of his plays from the Georgian period to today. In addition, Mulhallen offers details of the productions Shelley saw in England and Italy, many not identified before, as well as a vivid account of the actors and personalities that constituted the theatrical scene of his time. Her research reveals Shelley as an extraordinarily talented playwright, whose fascination with contemporary theatrical theory and practice seriously challenges the notion that he was a reluctant dramatist. Prof. Stephen Behrendt (Nebraska) has described the book as "wonderfully convincing" and "something wholly new in Shelley studies", while Prof. Tim Webb (Bristol) describes Mulhallen as having a "more precisely developed sense of the theatrical possibilities of Shelley's work than almost anybody who has written about Shelley". The Theatre of Shelley is essential reading for anyone interested in Romanticism, nineteenth-century culture and the history of theatre.